2017
DOI: 10.1108/jocm-11-2016-0253
|View full text |Cite
|
Sign up to set email alerts
|

Managing people and learning in organisational change projects

Abstract: Purpose: This article assesses the influence of people management practices on the outcomes of organisational change projects through their contributions to organisational learning. The contributions to their outcomes of particular corporate and project-specific people management practices are considered.Method: Case studies of two organisational change projects undertaken by Arts Council England during 2006-07 are used to examine how far and in what ways people management practices influence the outcomes of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
1
8
0
2
Order By: Relevance
“…This study confirms that those ethics officers who show more innovative work behavior are likely to achieve more effective ethics programs. This also matches Shaw’s (2017) conclusion that leading change requires explorative learning which, in turn, involves searching for innovation in order to refine existing ways of working. Hence, ethics officers must unite in their focus on ethics, innovation, and change so as to increase the impact of the ethics programs.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This study confirms that those ethics officers who show more innovative work behavior are likely to achieve more effective ethics programs. This also matches Shaw’s (2017) conclusion that leading change requires explorative learning which, in turn, involves searching for innovation in order to refine existing ways of working. Hence, ethics officers must unite in their focus on ethics, innovation, and change so as to increase the impact of the ethics programs.…”
Section: Discussionsupporting
confidence: 84%
“…Change programs, and their implementation, are often more open‐ended than linear (Weick & Quinn, 1999). Organizational change has been conceptualized as an example of organizational learning (Shaw, 2017). Shaw (2017) argues that change needs explorative learning, which involves searching for innovation; the aim is to refine the existing ways of doing things.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…McKinley and Lin, 2012), downsizing remains largely viewed as a negative organizational event (Datta and Basuil, 2015;Shaw, 2017), as noted earlier. Thus, drawing on fairness theory, we suggest that the downsizing event will trigger the Would counterfactual given that shareholders can likely imagine a more positive situation avoiding the downsizing event.…”
Section: Effect Of Downsizing Explanations On Market Reactionsmentioning
confidence: 78%
“…People management, therefore, becomes important. According to Shaw (2017), certain people management practices, individually and in combination, influence the outcomes of organizational change projects significantly through their contributions to organizational learning. In a three-firm study in the Kingdom of Saudi Arabia, Humaidan and Sabatier (2017) observed that depending on the orientation of the top management team (TMT), the managerial perception of the firm’s environment within the same scarcity situation leads to different strategic renewal responses.…”
Section: Policy Implicationsmentioning
confidence: 99%